War Science and Terrorism. - Richardson, Dr J. (Taylor and Francis, 2012)
Describes the application of research to the evolution of weapons. It shows how natural, engineering, information and environmental sciences are exploited how even social science is applied to recruitment, battlefield and logistical management, and careful preparation of terroristic acts.